Penerapan Sistem Pemasaran berbasis E-Commerce pada Produk Batik Tulis Dan Cap di Kelurahan Cipocok - Ahmad Dadan Hawari; Riki Gana Suyatna (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Banten Batik own distinctive characteristics _ And unique because it's on the side every the motive tell a story history legacy culture sultanate offerings in the form of culture , society sultanate Banten . In effort For conserve And protect batik then required introduction to world various various batik motifs in Indonesia and its history. Research qualitative emphasize exists complaint from Heritage batik craftsmen Banten in the Citra Gading Complex , Village Karundang , sub-district cipocok , city attack , against low sale of Heirloom batik Banten . In fact , the number of batik produced is not comparable with number of batik sold . It means more many batiks do not sold , compared to those sold . Temporary system sales carried out by Heritage batik craftsmen Banten in the complex image Gading , village Karundang , sub-district cipocok , city attack , banten , that is system sale conventional . Through promotion between batik craftsman , neighbor , nor batik buyers . The aim is to help , marketing system conventional This not enough maximum to sale of heirloom batik offer . So , it is necessary breakthroughs new For push sale of heirloom batik offer . Wrong One Current problem _ this , that is constraint on batik marketing , which continues experience decline . The reason is the height competition between batik craftsmen . So , total more batik production a lot , in comparison with batik sold , as long as this is the sales process use system Sale conventional . Promotion , take advantage fellow batik craftsmen as well batik buyers . Craftsman Not yet Can take advantage progress technology . So , reach market only limited local to Serang City . for push its height batik sales , with use system digital marketing sales . stages to be done in the digital marketing process of selling heirloom batik offer . including , making webset official special on the page specifically www.batikpusakabanten.com website This under control Heritage Batik Center Banten complex image Gading , sub-district Karundang, subdistrict cipocok , city attack . For speed up the promotion process And sales , then The website www.batikpusakabanten.com will be later will strengthened with it was formed account Facebook , Twitter, Instagram , and networking social other with the same theme buy batik.dalam webset that , too available features interesting , that's the goal For make it easier service ordering .